Hypertrophic Cardiomyopathy due to Mitochondrial Disease: Prenatal Diagnosis, Management, and Outcome - Lutgardo García-Díaz; Félix Coserria; Guillermo Antiñolo (Case Reports in Obstetrics and Gynecology)
A case of prenatally diagnosed fetal hypertrophic cardiomyopathy is reported. The mother was referred to our department at 37 weeks' gestation because of suspected congenital heart disease. Prenatal echocardiography showed biventricular hypertrophy and pericardial effusion, without additional abnormalities. Postnatal echocardiography confirmed prenatal diagnosis. Neonatal EKG showed biventricular hypertrophy and Wolff-Parkinson-White syndrome. Skeletal muscle biopsy was consistent with mitochondrial oxidative phosphorylation defect involving a combined defect of respiratory complexes I and IV. Echocardiographic followup during the first year of life showed progressive regression of hypertrophy and evolution to left ventricular myocardial noncompaction.